Analisis Tema Fantasi Komentar Donasi Palestina Pada Akun Youtube Nusantara Palestina Center - Susilawati, Lusi; Christin, Maylanny (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This research aims to examine the influence of actors' positions in communication networks and the role of fantasy themes in Palestinian donation comments on the Nusantara Palestine Center YouTube channel. Employing social network analysis through Labspolsys and Gephi 0.10, the study focuses on the video titled